THE CORRELATION AMONG PARENTS’ INVOLVEMENT, STUDENTS’ CONFIDENCE AND LEARNING ACHIEVEMENT OF ENGLISH - Putri, Talia Srikandi Malaya (Politeknik Negeri Sriwijaya, 2023)
This research is aimed to find out the correlation between parents’ involvement and students’ confidence, to find out the correlation between students’ confidence and learning achievement of English, to find out the correlation among parents’ involvement, students’ confidence and learning achievement of English. This research was a correlational study. The researcher used total sampling and the total samples were 131 students. The data collected through questionnaires about parents’ Involvement, and students’ confidence, also used a test for learning achievement of English. Further, the result of the coefficient correlation between parents’ involvement and students’ confidence was sig=<0.001, r=0.576 which means those variables were positively correlated. The correlation considered as medium correlation. Then, the result of correlation between students’ confidence and learning achievement of English was sig=<0.001, r=0.633 which means those variables were positively correlated. And the correlation considered as medium correlation. Last, correlation among parents’ involvement, students’ confidence and learning achievement of English. The result was sig=<0.001, r=0.580 which means that those variables were positively correlated. The correlation considered as medium correlation. Based on the result of data analyses, it can be concluded that those variables parents involvement, students’ confidence and learning achievement of English were positively correlated with medium correlation.